The study of the effect of the use of programming in the linear programming model (applied study) - ابراهيم, سميرة خليل (Journal of Economics and Administrative Sciences, 2010)
The parametric programming considered as type of sensitivity analysis. In this research concerning to study the effect of the variations on linear programming model (objective function coefficients and right hand side) on the optimal solution. To determine the parameter (θ) value (-5≤ θ ≤5).Whereas the result، the objective function equal  zero and the decision variables are non basic، when the parameter (θ = -5).The objective function value increases when the parameter (θ= 5) and the decision variables are basic، with the except of X24, X34.Whenever the parameter value increase, the objective function value increase and the basic variables are unchanged.